1979
DOI: 10.1159/000468382
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Lithiumbilanz während der Manie

Abstract: Lithium balance studies were performed in 19 patients suffering from mania and 6 patients suffering from depression. The following results were obtained: (1) The mean daily requirement for lithium in the manic patients was 52 mM, in those with depression 30 mM (additional requirement in manic patients 73%). (2) Renal elimination of lithium, after optimal blood lithium levels had been reached, was 76% in mania and 97% in depression (retention in manic patients 21%). (3) In mania there was an unchanged lithium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Further, the relationship found between renal lithium clearance and plasma lithium level, made possible a prediction of therapeutic lithium level on the basis of a test dose (Cooper et al, 1973;Rybakowski, 1984). However, the results of some studies still indicated that, despite unchanged renal clearance, lithium was retained more during mania, and manic patients needed more lithium to achieve the same plasma level (Almy and Taylor, 1973;Degkwitz et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the relationship found between renal lithium clearance and plasma lithium level, made possible a prediction of therapeutic lithium level on the basis of a test dose (Cooper et al, 1973;Rybakowski, 1984). However, the results of some studies still indicated that, despite unchanged renal clearance, lithium was retained more during mania, and manic patients needed more lithium to achieve the same plasma level (Almy and Taylor, 1973;Degkwitz et al, 1979).…”
Section: Introductionmentioning
confidence: 99%